2010
DOI: 10.3390/v20801530
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Influenza Virus Pathogenesis and Transmission

Abstract: Abstract:Influenza virus infection of humans results in a respiratory disease that ranges in severity from sub-clinical infection to primary viral pneumonia that can result in death. The clinical effects of infection vary with the exposure history, age and immune status of the host, and also the virulence of the influenza strain. In humans, the virus is transmitted through either aerosol or contact-based transfer of infectious respiratory secretions. As is evidenced by most zoonotic influenza virus infections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
364
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(368 citation statements)
references
References 198 publications
(254 reference statements)
3
364
0
1
Order By: Relevance
“…Notably, DBA mice are more susceptible to influenza infection than traditional mouse models, such as BALB/c, and thus replicate some aspects of severe disease in humans (12). In an attempt to account for the severity of this model, and to provide a reasonable comparison in cohorts receiving oseltamivir, the dose of VIS410 and oseltamivir was increased to 50 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, DBA mice are more susceptible to influenza infection than traditional mouse models, such as BALB/c, and thus replicate some aspects of severe disease in humans (12). In an attempt to account for the severity of this model, and to provide a reasonable comparison in cohorts receiving oseltamivir, the dose of VIS410 and oseltamivir was increased to 50 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the known genes downstream of TLR engagement (MYD88, IL6, IL1A, CXCL1), pathway analysis showed that the genes in the TLR-associated canonical antiviral response (P < 1.3 × 10 -12 , overlap 13/52) and IFN-I pathways (P < 2.5 × 10 -9 , overlap 8/24) were highly enriched (Supplemental Figure 8). This includes CXCL9, ifestation of infection in these animals (41,43). While the vehicle-treated animals exhibited significant weight loss within 3 days after viral infection ( Figure 2H), reaching a maximum weight loss around day 6, before regaining it, LA1-treated animals did not show any loss of body weight after infection.…”
Section: Cd11bmentioning
confidence: 91%
“…[120][121][122][123][124][125] Studies on animal models of influenza infection in pregnancy are limited. Here, we focus on studies in mice and nonhuman primate (cynomolgus macaque).…”
Section: Animal Studiesmentioning
confidence: 99%